SAT0025 The Association Serum Interleukin 17 and Interleukin 23 Levels with Clinical and Radiological Parameters in Rheumatoid Arthritis Patients - Ucar, U.; Duruoz, M. T.; Guvenc, Y.; Orguc, S. (Annals of the rheumatic diseases, 2013)
Background Rheumatoid arthritis (RA) is a chronic, inflammatory disease which causes symmetrical destructive changes in diartrodial synovial joints (1). Cytokines play an important role in RA pathogenesis. Th 17 cells are T lymphocytes which produce IL-17. Th 17 cells express the IL 23 receptor on their membrane and are dependent on this cytokine for their survival and expansion (2). Objectives In this study, our aim was to determine serum levels of IL-17A, IL-17B, IL-17C, IL-17F and IL-23 in RA patients and to investigate the association of these cytokines with clinical, laboratory and radiological parameters in RA. Methods Seventy RA patients fulfilling 1987 ACR criteria and control group of 41 volunteers (20 OA patients and 20 healthy subjects) were enrolled in the study. Patients and control group serum IL-17A, IL-17B, IL-17C, IL-17F and IL-23 levels were measured with ELISA method. RA patients’ plain radiographic images of bilateral hands were scored (modified Sharp Van der Heijde method) also edema and erosion scores (RA MRI scoring (RAMRIS) system) of hand and wrist MRI scans of the most affected side were calculated. The association between serum levels of IL-17 and IL-23 with clinical, laboratory and radiological findings in RA were evaluated. Results Serum IL-23 levels of RA patients were significantly higher than control group. There was no significant difference for serum IL-17(A-C,F) levels between RA patients and control group. No significant difference could be found between IL-17(A-C,F) levels of control subjects and RA patients when grouped for DAS 28 score (remission, low, moderate and high disease activity). On the other hand serum levels of IL-23 were significantly higher in all RA groups compared with controls. No correlations were found between IL-17(A-C,F) and IL-23 levels and disease duration, quality of life and functional status scores, Sharp Van der Heijde score and laboratory parameters. There was a moderate positive correlation between IL-17A, IL-17C levels and both wrist and total edema MRI scores. When RA patients were divided into two groups according to MRI edema scores it was found that levels of IL-17A and IL-17F were significantly higher in the group with higher edema scores. Conclusions Our results showed that, inspite of being a useful marker to support the diagnosis of RA, IL-23 does not give additional information about disease activity in RA patients. It is known that IL-17 is higher at early phases and acute attacks rather than late phases in RA patients. We also found that serum levels of IL-17A, IL-17B, IL-17C, IL-17F were similar between patients most of whom had established RA and control group. On the other hand, our data showing that patients with higher IL-17A and IL-17F levels had higher MRI edema scores, allowed us to think that these cytokines could be used as a marker of acute attacks and a parameter for prediction of preerosive and destructive changes and rapid disease progression. References Kvien T, Scherer HU, Burmester G. Rheumatoid Arthritis. In: Bijlsima JWJ editors. Eular Compendium on Rheumatic Diseases. 1st ed. Italy: BMJ publishing group;2009. p. 61-80. Lubberts E. Th17 cytokines and arthritis. Semin Immunopathol 2010;32:43-53 Disclosure of Interest None Declared